-9r+10=8+3r

Simple and best practice solution for -9r+10=8+3r equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -9r+10=8+3r equation:


Simplifying
-9r + 10 = 8 + 3r

Reorder the terms:
10 + -9r = 8 + 3r

Solving
10 + -9r = 8 + 3r

Solving for variable 'r'.

Move all terms containing r to the left, all other terms to the right.

Add '-3r' to each side of the equation.
10 + -9r + -3r = 8 + 3r + -3r

Combine like terms: -9r + -3r = -12r
10 + -12r = 8 + 3r + -3r

Combine like terms: 3r + -3r = 0
10 + -12r = 8 + 0
10 + -12r = 8

Add '-10' to each side of the equation.
10 + -10 + -12r = 8 + -10

Combine like terms: 10 + -10 = 0
0 + -12r = 8 + -10
-12r = 8 + -10

Combine like terms: 8 + -10 = -2
-12r = -2

Divide each side by '-12'.
r = 0.1666666667

Simplifying
r = 0.1666666667

See similar equations:

| 10-5(9n-9)=10 | | 4x^2-x-29=0 | | 5/20=9/x | | 18a^2-48a+32=0 | | x+-5=2x+1 | | -3(2x+7)=-6x-21 | | 1.5(m-3)=12 | | 2x+y=3.5 | | 3secx-5=-8 | | 3(2p+1)=7(-p)-6 | | x^2-4x^1+3=0 | | 3.4c-17=68 | | 9y=-x+9 | | -28(z-73)=z+6 | | 13x+5y=17 | | 6x+4x+4+8=5x+3+4x | | 4a^2+19a+12=0 | | (7.1)1.9= | | -2y+3=-9 | | -2y+3=-8 | | 5g+4(-8+5g)=1-g | | 74y-4884=y+(-72) | | 74y-4884=y+(-74) | | A-10=34 | | 16x-1.86x^2=0 | | (3x^2-5x)-(x^2+4x+3)= | | y=20+5x | | A=2400+144t | | 2(6z+1)-6=92 | | 7/8=y/56 | | 1.5y=1.25 | | 2h+7=2(h+2)+3 |

Equations solver categories